2013
DOI: 10.5267/j.ijiec.2013.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Application of response surface methodology on investigating flank wear in machining hardened steel using PVD TiN coated mixed ceramic insert

Abstract: The paper presents the development of flank wear model in turning hardened EN 24 steel with PVD TiN coated mixed ceramic insert under dry environment. The paper also investigates the effect of process parameter on flank wear (VBc). The experiments have been conducted using three level full factorial design techniques. The machinability model has been developed in terms of cutting speed (v), feed (f) and machining time (t) as input variable using response surface methodology. The adequacy of model has been chec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…They concluded that the developed relationship can be effectively used to predict flank wear of carbide tool at a confidence level of 95%. Sahoo et al [6], confirmed this conclusion when studying the development of flank wear model in turning hardened EN 24 steel with PVD TiN coated mixed ceramic insert under dry environment. …”
supporting
confidence: 67%
“…They concluded that the developed relationship can be effectively used to predict flank wear of carbide tool at a confidence level of 95%. Sahoo et al [6], confirmed this conclusion when studying the development of flank wear model in turning hardened EN 24 steel with PVD TiN coated mixed ceramic insert under dry environment. …”
supporting
confidence: 67%
“…RSM model can be effectively utilized to predict the surface roughness in turning D2 steel. Sahoo et al (2013) developed flank wear model in turning hardened EN 24 steel with PVD TiN coated mixed ceramic insert under dry environment. Machining time has been found to be the most significant parameter on flank wear followed by cutting speed and feed as observed from main effect plot and ANOVA study.…”
Section: Review Of Literature and Objectivesmentioning
confidence: 99%
“…The lower surface roughness value indicates that the machining forces are lesser during the trials and the smooth machining of EN24 alloy steel workpiece is obtained. 24,25 Surface¯nish is a signi¯cant index of machinability. The surface conditions of the machined component depend on its service life.…”
Section: Surface Roughness Analysismentioning
confidence: 99%